0.9x-0.3(4-x)=6.6

Simple and best practice solution for 0.9x-0.3(4-x)=6.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.9x-0.3(4-x)=6.6 equation:


Simplifying
0.9x + -0.3(4 + -1x) = 6.6
0.9x + (4 * -0.3 + -1x * -0.3) = 6.6
0.9x + (-1.2 + 0.3x) = 6.6

Reorder the terms:
-1.2 + 0.9x + 0.3x = 6.6

Combine like terms: 0.9x + 0.3x = 1.2x
-1.2 + 1.2x = 6.6

Solving
-1.2 + 1.2x = 6.6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.2' to each side of the equation.
-1.2 + 1.2 + 1.2x = 6.6 + 1.2

Combine like terms: -1.2 + 1.2 = 0.0
0.0 + 1.2x = 6.6 + 1.2
1.2x = 6.6 + 1.2

Combine like terms: 6.6 + 1.2 = 7.8
1.2x = 7.8

Divide each side by '1.2'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| 2x-11=y | | 6(3+x)=5(x-6) | | 4a=2(a+2)-12 | | y-3=2(-1+1) | | 7(10)+7(10)+12(10)=360 | | 3+x+5-2x=78 | | 4x(2x-7)=112 | | 3x+5[2-4(x-2)]=x-4 | | 24v^4+78v^3b-21v^2b^2=0 | | Y=2ax-9x-9b | | 3+x-5+2x=78 | | -3[x+(-8)]=56 | | 4x+17=2x | | 126=10+4p | | 7x+42=-18-3x | | F(x)=11x-1 | | [x-2]=-2 | | 195=12+x | | 2y=103-x | | 5(x+5)+8(-x+8)=77 | | 3x-15+6x+1=45 | | -4(x-1)=9x+9 | | .5(10+12n)=.3333(15n+15) | | -4(x+6)=-4(x+2)-x | | 8(5c-1)-18=38c+8 | | -1=t+(-18) | | 8c^2-20c-12=0 | | 3.5(9)+3.5(9)+12(9)=180 | | 9x-6x-2=1 | | y=x^3-13x | | 7x+1=-2x+37 | | 6t+3(5t-4)=12(2t-2w) |

Equations solver categories